2021
DOI: 10.1016/j.jiph.2021.06.021
|View full text |Cite
|
Sign up to set email alerts
|

Bullous drug eruption after second dose of mRNA-1273 (Moderna) COVID-19 vaccine: Case report

Abstract: Background In December 2020, Moderna released the mRNA-1273 vaccine. The most common side effects are headache, muscle pain, redness, swelling, and tenderness at the injection site. In addition, there have been dermatological adverse events, such as hypersensitivity reactions. Although rare, various bullous eruptions have been described following vaccination. Bullous pemphigoid has been reported to occur most often after receipt of influenza and the diphtheria-tetanus-pertussis vaccine. To the bes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 6 publications
2
36
0
2
Order By: Relevance
“…Stevens-Johnson syndrome has been associated with immunotherapy, 24 but a causal association with COVID-19 vaccination cannot be excluded with three cases of Stevens-Johnson syndrome after vaccination reported in the published literature so far. 25 , 26 , 27 Although it is conceivable that treatments that boost the immune system, such as vaccination, might contribute to immune-related adverse events in patients treated with immunotherapy, the incidence of such adverse events did not seem to be higher after vaccination and were in line with the expected rate in patients receiving immunotherapy and those receiving chemoimmunotherapy. In another study, no immune-related adverse events were reported in 134 patients treated with immunotherapy who received the BNT162b2 vaccine.…”
Section: Discussionmentioning
confidence: 82%
“…Stevens-Johnson syndrome has been associated with immunotherapy, 24 but a causal association with COVID-19 vaccination cannot be excluded with three cases of Stevens-Johnson syndrome after vaccination reported in the published literature so far. 25 , 26 , 27 Although it is conceivable that treatments that boost the immune system, such as vaccination, might contribute to immune-related adverse events in patients treated with immunotherapy, the incidence of such adverse events did not seem to be higher after vaccination and were in line with the expected rate in patients receiving immunotherapy and those receiving chemoimmunotherapy. In another study, no immune-related adverse events were reported in 134 patients treated with immunotherapy who received the BNT162b2 vaccine.…”
Section: Discussionmentioning
confidence: 82%
“…The blistering rash appeared after the first dose and worsened after the second dose [53]. Finally, one case of extensive bullous fixed drug eruption was reported the day after the second dose of the Moderna vaccine [54].…”
Section: Severe Cutaneous Adverse Reactions (Scars)mentioning
confidence: 97%
“… 4 In the literature, various cutaneous conditions have been observed including anecdotal cases of erythema multiforme with morbilliform rash, delayed‐type hypersensitivity reaction, bullous drug eruption, pernio/chilblains (eg, “COVID toes”), erythromelalgia, and pityriasis‐rosea‐like exanthems, and herpes zoster (HZ). 5 , 6 , 7 , 8 Studies have reported development of herpes zoster due to SARS‐CoV‐2 infection either at the time of disease progression or following recovery from the disease. In the context of COVID‐19 pandemic, studies observed that COVID‐19 is associated lymphopenia, particularly CD3+, CD8+ lymphocytes, and functional impairment of CD4+ T cells, might make a patient more vulnerable to development of herpes zoster.…”
Section: Introductionmentioning
confidence: 99%